The rain forest - Jackson, Tom, 1972-; Bracken, Carolyn (New York, NY : Scholastic Inc., 2015)
Ms. Frizzle and her class explore the rainforest, including the plants and animals that live there.
"A nonfiction companion to the original Magic School Bus series"--Front cover.
"Based on The Magic School Bus series"--T.p. verso.
3.0
K-3
K-3
Keywords: Rain forests -- Juvenile literature; Rain forest ecology -- Juvenile literature; Rain forests; Rain forest ecology; Rain forests; Rain forest ecology